The Role of Organizational Design in Enhancing Employee Motivation in Saudi Arabia - Mohammad Dasseh, Mohammad Yousef (2016)
Previous research reveals that the centralized, bureaucratic and rigid authority lines are the main features in the Saudi work environment. Researchers have studied several HRM topics in Saudi Arabia such as leadership, regulations and the impact of culture on employees. However, there seems to be a lack of attention to topics related to motivation, empowerment and organizational design. This paper aimed to explore the factors that motivate employees, investigate the relationship between organizational design and employee motivation and study the organization’s initiatives to improve employee motivation in the context of Saudi Arabia. The complex and subjective nature of the topic required the use of a qualitative approach. This researcher conducted fifteen semi-structured interviews with employees and managers holding different positions in various fields in Saudi Arabia. The study found that employees’ motivation was significantly influenced by factors at three levels, the national level (e.g. Wasta, Saudization and the country’s culture), the organizational level (e.g. manager’s attitude, centralization and the career progression clarity) and on the employee level (e.g. financial incentives, significance and autonomy of their tasks, self-motivation, and dynamic motivation). Although employees’ motivation boosted when they were delegated more authority (empowered), in most cases, for others authority meant being responsible on a larger scale (which made them fear making fatal mistakes) and they preferred to have less authority unless they were educated about their tasks. Though participants lacked awareness regarding their organizations’ initiatives to improve motivation, they provided plenty of information regarding the Ministry of Labour’s plans to protect employees and impede any practices violating employees’ rights. The study found that the Ministry of Labour has several insightful initiatives (e.g. training, women’s opportunities in the workplace and computerizing systems). However, improvements in the implementation of their programs are necessary for the country’s international business development and the welfare of employees.